2021
DOI: 10.1016/j.jcot.2021.03.023
|View full text |Cite
|
Sign up to set email alerts
|

Mortality escalates in patients of proximal femoral fractures with COVID-19: A systematic review and meta-analysis of 35 studies on 4255 patients

Abstract: Background Concerns have been raised about the escalated mortality in patients of proximal femoral fractures (PPFs) with COVID-19. A meta-analysis to evaluate mortality in patients with PPFs managed during the current COVID-19 pandemic was conducted. Methods A systematic review and meta-analysis of all published studies were conducted with a search on PubMed, Scopus, Web of Science, and Cochrane Library databases using appropriate keywords from January 01, 2020 to Janua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 65 publications
(184 reference statements)
0
11
0
Order By: Relevance
“…COVID 19+ patients had a lower overall survival probability than COVID 19-patients (Figure 3). Similarly, COVID 19+ patients had longer discharge probability with a longer time to discharge (Median [IQR] = 5 [4][5][6][7] vs. 3 [3][4] days) compared to COVID 19-patients (Figure 3).…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…COVID 19+ patients had a lower overall survival probability than COVID 19-patients (Figure 3). Similarly, COVID 19+ patients had longer discharge probability with a longer time to discharge (Median [IQR] = 5 [4][5][6][7] vs. 3 [3][4] days) compared to COVID 19-patients (Figure 3).…”
Section: Resultsmentioning
confidence: 92%
“…Several studies have shown the deleterious effects of COVID-19 on patients with orthopedic trauma. [3][4][5] Other studies on the impact of the pandemic on trauma centers and outcomes of trauma patients revealed an increased risk of mortality, longer length of stay and pulmonary complications in COVID-19 positive (COVID 19+) patients, along with fewer traumatic blunt injury encounters. 6,7 Increased complications have also been seen in other surgical COVID 19+ patients as compared to COVID-19 negative (COVID 19-) patients; mainly pulmonary in nature, followed by multi-organ complications.…”
Section: Introductionmentioning
confidence: 99%
“…The Robert Koch Institute informed weekly about the increasing number of SARS-CoV‑2 outbreaks in German hospitals [ 20 ]. Significant higher mortality rates were reported for patients undergoing emergency and elective surgery [ 6 , 7 , 13 , 17 ]. In the absence of vaccines and specific treatment for the COVID-19 disease, preventive strategies had to be implemented to protect our patients, especially the vulnerable groups.…”
Section: Discussionmentioning
confidence: 99%
“…However there was increased in number mortality in proximal femoral fractures in elderly age group. Patralekh et all have done a systematic review in 4355 patients with proximal femoral fractures and reported increased mortality in COVID 19 positive patients and the reason was shown to cytokine storm post operatively [13] The recent COVID 19 pandemic is expected to continue for coming years. However high patient load compare to healthcare infrastructure is always challenging in India.…”
Section: Discussionmentioning
confidence: 99%